Receptor-Interacting Protein Kinase 3 Inhibition Relieves Mechanical Allodynia and Suppresses NLRP3 Inflammasome and NF-κB in a Rat Model of Spinal Cord Injury - Xue, Song; Cao, Zhen-xin; Wang, Jun-nan; Zhao, Qing-xiang; Han, Jie; Yang, Wen-jie; Sun, Tao (Frontiers in Molecular Neuroscience, 2022)
Abstract Background: Neuroinflammation is critical in developing and maintaining neuropathic pain after spinal cord injury (SCI). The receptor-interacting protein kinase 3 (RIPK3) has been shown to promote inflammatory response by exerting its non-necroptotic functions. In this study, we explored the involvement of RIPK3 in neuropathic pain after SCI. Methods: Thoracic (T10) SCI rat model was conducted, and the mechanical threshold in rats was measured. The expressions of RIPK3, NLRP3, caspase-1, and NF-κB were measured with western blotting analysis or qRT-PCR. Immunohistochemistry staining was used to explore the co-labeled NLRP3 with NeuN, GFAP, and Iba1. In addition, ELISA was applied to analyze the levels of pro-inflammatory factors IL-1β, IL-18, and TNF-α. Results: The expression of RIPK3 was elevated from postoperative days 7 to postoperative days 21, which was consistent with the development of mechanical allodynia. Intrathecal administration of RIPK3 inhibitor GSK872 could alleviate the mechanical allodynia in SCI rats and reduce the expression levels of RIPK3. The activation of NLRP3 inflammasome and NF-κB were attenuated by GSK872 treatment. Immunofluorescence furthermore suggested that NLRP3 had colocalization with glial cells and neurons in the L4–L6 spinal dorsal horns. In addition, GSK872 treatment reduced the production of inflammatory cytokines. Conclusion: Our findings indicated that RIPK3 was an important facilitated factor for SCI-induced mechanical allodynia. RIPK3 inhibition might relieve mechanical allodynia by inhibiting NLRP3 inflammasome, NF-κB, and the associated inflammation.